Analysis of Jinayah Fiqh on the Role of Visum Et Repertum in Proving the Crime of Persecution - Diah Ayu Lestari; Aris Aris; Wahidin Wahidin (Program Studi Hukum Pidana Islam IAIN Parepare, 2022)
This study aims to determine the role of Visum et Repertum in proving criminal acts in the case of decision no. 141/Pid.B/2020/PN.Pin and to find out the position of Visum et Repertum in Islamic Criminal Law. Visum et Repertum evidence is evidence in the form of a letter, which has the same position as a tool that has the same power at trial. The results of the examination in the form of Visum et Repertum are very important in committing criminal acts, especially criminal acts such as in the case of decision no. 141.B/2020/PN.Pin. Evidence of Visum et Repertum can be interpreted as Qorinah. the position of Visum et Repertum as the application of Ijtihad for judges to get the real truth and also get justice.